Suicide and Traumatic Brain Injury Among Individuals Seeking Veterans Health Administration Services Between Fiscal Years 2006 and 2015. Issue 5 (September 2019) - Hostetter, Trisha A.; Hoffmire, Claire A.; Forster, Jeri E.; Adams, Rachel Sayko; Stearns-Yoder, Kelly A.; Brenner, Lisa A.
Abstract : Objective: Examine associations between traumatic brain injury (TBI) and (1) suicide and (2) suicide method among individuals receiving Veterans Health Administration (VHA) care. Setting: VHA, Fiscal Years 2006-2015. Participants: Veterans with a TBI diagnosis during/prior to the study window ( n = 215 610), compared with a 20% random sample of those without TBI ( n = 1 187 639). Design: Retrospective, cohort study. Cox proportional hazards models were fit accounting for time-dependent measures, chronic conditions, and demographics for those with TBI compared with those without. Additional models evaluated the impact of TBI severity on the association between TBI and suicide, and method. Main Outcome Measures: Death by and method of suicide. Results: The hazard of suicide was 2.19 times higher for those with TBI than for those without TBI (95% CI = 2.02-2.37), and was still significant after accounting for covariates (hazard ratio [HR] = 1.71; 95% confidence interval [CI] = 1.56-1.87). Considering severity, mild TBI compared with no TBI was significantly associated with an elevated hazard of suicide, after adjusting for covariates (HR = 1.62; 95% CI = 1.47-1.78). There was also a significant difference in death by suicide between moderate/severe TBI when compared with no TBI, after adjusting for covariates (HR = 2.45; 95% CI = 2.02-2.97). Moderate/severe TBI was significantly associated with an increase in the odds of suicide by firearm among decedents (odds ratio = 2.39; 95% CI = 1.48-3.87). Conclusion: Traumatic brain injury is associated with an elevated risk for suicide. Particular concern is warranted for those with moderate/severe TBI. Lethal means safety should be explored as an intervention. Abstract : Supplemental Digital Content is Available in the Text.